Values and Concepts of Multicultural Education in Hindu Religious Education According to Teachings Vasudhaiva Kutumbakam - Suwadnyana, I Wayan; Danaswara, I Putu Gede Budhi; Karsana, I Nyoman; Goh, Jimmu; Permana Putri, I Gusti Ayu Hyudha (PT. Publikasiku Academic Solution, 2025)
Multicultural education is a crucial approach in creating a harmonious and inclusive society, especially in Indonesia, which is rich in cultural, ethnic, and religious diversity. This article discusses the values of multicultural education in the context of Hindu religious education, referring to the principle of Vasudhaiva Kutumbakam, which emphasizes that the whole world is one family. Through multicultural education, individuals are taught to appreciate and understand differences, as well as to internalize the noble values contained in Hindu teachings. However, the implementation of multicultural education is not without challenges. Various internal factors influence its success, such as the quality of educators, teaching methodologies, and openness to diversity. Additionally, external factors such as family support, social interactions, and government policies play a significant role in creating a conducive learning environment. Therefore, synergy among educators, students, families, communities, and the government is essential to achieve success in implementing multicultural education, thereby fostering a generation that is tolerant and respectful amidst existing diversity.